Institute of common ownership right of France, Germany, Switzerland and the Netherlands - Uteubayev, T.T.; Kizdarbekova, A.S. (Bulletin of the Karaganda University “Law Series”, 2018)
The features of the common property institution in the codifications of France, Germany, Switzerland and the Netherlands, which form the basis of the General Part of the Civil Code of the Republic of Kazakhstan, are considered in the article. The peculiarity of these civil codifications is that the recited norms of Roman private law coexisted in them along with national norms. The implementation and development of these rules led to the fact that over time taking into account some specifics in most countries two codifications German and French were developed in European countries. In accordance with them, the rules on common property were also developed. The work indicates that common property in the legislation of European states is characterized by the existence of a common right to common property, which is not unique, because its implementation depends on the will of other co-owners, which is a kind of restriction of the right of each participant to common property and the right to share, the implementation of which does not depend on the will of other members of the community, however, in some cases, requires the observance of certain rules - the preemption right. In addition, a legal community in European jurisdictions arises either on the basis of a contract, or by virtue of the law, it has both a real and a binding nature, it can be shared or joint. The principle of majority, and the principle of unanimity, which is used at making decisions on the management of property in common ownership is characterized both for the countries of Europe.